EFFECT OF THE CUTTING AGE OF Brachiaria decumbens ON RUMEN FUNCTIONS AND in vitro GAS PRODUCTION - M. Andino; M. Barros-Rodriguez; J.C. Vargas Burgos; V. Andrade-Yucailla; Nestor Acosta-Lozano; R. Aragadvay-Yungan; S. Mayorga-Paredes (Tropical and Subtropical Agroecosystems, 2019)
The aim was to evaluate the effect of cut age on ruminal function and in vitro gas production of Brachiaria decumbens grass. Eighteen parcels established with B. decumbens were used. For each treatment, T1: 45, T2: 60 and T3: 75 (cut days), the chemical composition, rumen degradation, digestibility, pH, ammonia, volatile fatty acids (VFA) and gas production were analyzed. It was observed higher (P <0.05) effective degradation (58%; 0.02 k, 45%; 0.05 k and 38%; 0.08 k) and apparent digestibility (57%) at 45 days of cut. The ruminal pH was maintained between 6.99 to 7.51 from 6 h to 24 h post incubation between the different cut ages (P <0.05). With respect to NH3-N it was higher at 45 and 60 days (27.3 and 25.6 mg/L respectively). The VFA did not show differences between the treatments evaluated (P> 0.05). The lowest (P = 0.0001) gas production was observed in the B. decumbens cut at 45 days (T1). It can be concluded that the best age for grazing of B. decumbens can be between 45 and 60 days of regrowth.